Fuzzy Synthetic Evaluation Model on Cultural Characteristics behind People’s Selection of Subway - Ruijie Mu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Taking Zhengzhou urban residents travel means and the city’s traffic conditions as examples, this paper makes in-depth analysis on the Cultural Characteristics behind options of Zhengzhou citizen’s travel means. The paper, after investigating the citizen’s travel intentions, makes both normative and empirical comparisons to different cultural features behind people choosing different urban travel means. Then it drew a conclusion on how different cultural characteristics of urban residents affect their preference to travel means. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4171